A COMPARATIVE STUDY ON PREFERRED LEARNING STYLE BETWEEN AUDITORY AND KINESTHETIC LEARNERS ON READING ACHIEVEMENT - Puji Endah Hastuti (Language-Edu, 2021)
Students would vary on how successful they were in learning foreign language since they were affected by their individual differences. Learning styles as one category of individual differences was investigated and this study determined two kinds of learning styles namely auditory and kinesthetic. This study intended to compare between auditory and kinesthetic learners on reading achievement. Conducted on even semester 2019/2020 academic year in SMA Islam NU Pujon, Malang. The outcome of the analysis showed that the t-score = -608, p = .549 was the result of an independent t-test and the results indicated that the reading achievement between auditory and kinesthetic learners was not significantly different (p = .549 > 0.05). It could be concluded that the preferred learning style did not influence their reading comprehension for there might be other factors such as cognitive process. However, the teacher should know the students’ learning styles as the consideration in determining the teaching strategies that would suitable for all learning styles. In addition, learning styles might influence other skills, namely speaking, writing or listening. Thus, these topics might be a further discussion beyond leaning styles that would be investigated by other researchers